2007
DOI: 10.1021/ac062034g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry and Electrocatalytic Properties of Hemoglobin in Layer-by-Layer Films of SiO2 with Vapor−Surface Sol−Gel Deposition

Abstract: In this paper, layer-by-layer {Hb/SiO2}n films assembled by alternate adsorption of positively charged hemoglobin (Hb) and vapor-surface sol-gel deposition of silica at 50 degrees C onto a glassy carbon electrode were reported. The result films were characterized with cyclic voltametery, electrochemical impedance spectroscopy, UV-vis spectroscopy, and SEM, and the direct electrochemical and electrocatalytic properties of Hb in these layer-by-layer films were investigated. A pair of well-defined quasi-reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Thus, the electrochemical investigations have been mainly performed with adding of mediators and promoters or modified and immobilized electrodes, i.e. by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the electrochemical investigations have been mainly performed with adding of mediators and promoters or modified and immobilized electrodes, i.e. by the MET types (Kafi and Crossley, 2013;Yin et al, 2005;Revenga-Parra et al, 2005;Topoglidis et al, 2003;Kawahara and Ohno, 1998;Shan et al, 2007;Shi et al, 2007;Zhao et al, 2006;Feng et al, 2006;Zhang and Oyama, 2004;Jia et al, 2004;Sun and Hu, 2004;Gu et al, 2001). On the other hand, we have demonstrated a simplest DET between Hb molecules and bare indium-tin-oxide (ITO) electrodes and found that the protein structure of Hb molecules on the bare ITO electrode surface should be similar to its own native state the same as that in the solution phase (Ayato et al, 2008;Ayato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, inaccessibility of the heme group, buried in a large three-dimensional protein shell, and electrode passivation due to protein adsorption make it difficult to establish direct electron transfer between Hb and conventional electrodes. [3] To solve these problems, various modification methods and nanostructured materials have been used to obtain a direct electrochemical response from Hb, including inorganic nonmetallic materials, [2a, 3-6] nano metal oxides, [7,8] macroporous gold films, [1] and electrodes modified with organic compounds. [9][10][11][12][13] Due to the unique structures of these materials, immobilized Hb molecules retaining their native structure can communicate directly with the modified electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[3, 12b, 13, 25, 36, 37] The small K app m value indicates that the immobilized Hb on the MPPA/Au electrode has a high biological affinity for H 2 O 2 [38] and higher catalytic activity for reduction of H 2 O 2 . [3] Repeating ten measurements with the Hb/MPPA/Au electrode in 3.0 10 À5 m H 2 O 2 gave a relative standard deviation of 3.8 %, that is, the Hb/MPPA/Au electrode has excellent reproducibility.…”
mentioning
confidence: 97%
“…[32] The impedance responses over a wide range of frequencies can be accurately fitted by using the classical Randles circuit displayed in Figure 3B. The parameters R W and W corre- spond to the uncompensated resistance and Warburg impedance for semi-infinite linear diffusion, C int is the doublelayer capacitance, and R ct (the charge-transfer resistance) is related the electron-transfer kinetics of the redox probe ([Fe(CN) 6 ] 3À /[Fe(CN) 6 ] 4À ) at the electrode interface and can be estimated from the diameter of the semicircular part (higher frequency) of the EIS curve, as described below.…”
Section: Resultsmentioning
confidence: 99%